PROBLEMATICS OF CONTEMPORARY FIQH MUNAKAH: ONLINE LENDING AS FAMILY SUSTENANCE BUKITTINGGI STUDY - Elfiani, Elfiani; Rahmiati, Rahmiati; Naali, Basri; Hendri, Hendri; Amin, Saiful (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2025)
As time progresses, nafkah can be obtained from various sources, including online loans, where there are differences in scholarly opinion about the law. So the formulation of the problem in this study is how the motivation of the community to make online loans for family nafkah in Bukittinggi, and how the views of Islamic law and positive law about online loans for family nafkah in Bukittinggi. Based on the results of the study, the motivation of the community to make online loans in fulfilling family maintenance is urgent needs, easy disbursement, easy requirements and consumptive behavior. While providing maintenance from online loans in the view of Islamic law is permissible based on urgent needs, such as health, children's education costs, sudden household needs and if it meets the conditions, namely that the online loan is legal and in accordance with Islamic law.